Membrane guanylyl cyclase complexes shape the photoresponses of retinal rods and cones - Wen, Xiao-Hong; Dizhoor, Alexander M; Makino, Clint L (Frontiers in Molecular Neuroscience, 2014)
In vertebrate rods and cones, photon capture by rhodopsin leads to the destruction of cyclic GMP (cGMP) and the subsequent closure of cyclic nucleotide gated ion channels in the outer segment plasma membrane. Replenishment of cGMP and reopening of the channels limit the growth of the photon response and are requisite for its recovery. In different vertebrate retinas, there may be as many as four types of membrane guanylyl cyclases (GCs) for cGMP synthesis. Ten neuronal Ca2+ sensor proteins could potentially modulate their activities. The mouse is proving to be an effective model for characterizing the roles of individual components because its relative simplicity can be reduced further by genetic engineering. There are two types of GC activating proteins (GCAPs) and two types of GCs in mouse rods, whereas cones express one type of GCAP and one type of GC. Mutant mouse rods and cones bereft of both GCAPs have large, long lasting photon responses. Thus, GCAPs normally mediate negative feedback tied to the light-induced decline in intracellular Ca2+ that accelerates GC activity to curtail the growth and duration of the photon response. Rods from other mutant mice that express a single GCAP type reveal how the two GCAPs normally work together as a team. Because of its lower Ca2+ affinity, GCAP1 is the first responder that senses the initial decrease in Ca2+ following photon absorption and acts to limit response amplitude. GCAP2, with a higher Ca2+ affinity, is recruited later during the course of the photon response as Ca2+ levels continue to decline further. The main role of GCAP2 is to provide for a timely response recovery and it is particularly important after exposure to very bright light. The multiplicity of GC isozymes and GCAP homologs in the retinas of other vertebrates confers greater flexibility in shaping the photon responses in order to tune visual sensitivity, dynamic range and frequency response.